Identification of a T-cell-specific transcriptional enhancer located 3' of C gamma 1 in the murine T-cell receptor gamma locus. - Spencer, D M (1991)
A transcriptional enhancer element has been localized 3 kilobases 3' of the murine T-cell receptor C gamma 1 locus using a chloramphenicol acetyltransferase reporter gene construct. As a monomer the enhancer functions only in PEER gamma delta cells and Jurkat alpha beta cells of the T-cell lines tested. However, a tetramer of the enhancer functions in virtually all T-cell lines tested, including alpha beta T-cell lines, but not in other cell types. These results suggest that elements other than the enhancer are responsible for the failure of rearranged C gamma 1 genes to be expressed in alpha beta T cells. The enhancer has been localized to a 200-base-pair Rsa I restriction fragment, which contains sequence motifs similar to those found in the other T-cell receptor enhancers but not in the immunoglobulin enhancers.